Time in Range, as a Novel Metric of Glycemic Control, Is Reversely Associated with Presence of Diabetic Cardiovascular Autonomic Neuropathy Independent of HbA1c in Chinese Type 2 Diabetes. (6th February 2020) - Guo, Qingyu; Zang, Pu; Xu, Shaoying; Song, Wenjing; Zhang, Zhen; Liu, Chunyan; Guo, Zhanhong; Chen, Jing; Lu, Bin; Gu, Ping; Shao, Jiaqing
Abstract : Objective . The objective of this study is to investigate the relationship between time in range (TIR), a new metric of continuous glucose monitoring (CGM) and cardiovascular autonomic neuropathy (CAN) in individuals with type 2 diabetes mellitus (T2DM). Methods . A total of 349 individuals with T2DM were enrolled in this study. Evaluating by the standard cardiac autonomic reflex tests (CARTs), there were 228 diabetic individuals without cardiovascular autonomic neuropathy (without confirmed CAN) including absent CAN (n = 83 cases) and early CAN (n = 145 cases) and 121 diabetic individuals complicated with cardiovascular autonomic neuropathy (CAN) including definite CAN (n = 109 cases) and severe CAN (n = 12 cases). All patients underwent 3-day CGM. TIR is defined as the time percent during a 24-hour period when the glucose is in the range of 3.9-10 mmol/L. The Spearman analysis was used to analyze the correlation between TIR and CART parameters, total CAN score. The logistic regression was applied to analyze the relationship between TIR and CAN by adjusting for the age, duration of diabetes, sex, lipid situation, serum creatinine, body mass index, blood pressure, HbA1c (%), and other glycemic variability (GV) metrics. Results . The total presence of CAN was 34.67% (definite CAN 31.23% and severe CAN 3.44%). Patients with more severe CAN had lower TIR (P < 0.001 ). With increasing quartiles of TIR, the presence of CAN by severity declined (P < 0.05 ). TIR is inversely correlated with total score of CAN (P < 0.001 ) and positively associated with heart rate variation during the lying to standing, Valsalva maneuver, and deep breathing (P < 0.05 ). The logistic regression found a robust association between TIR and CAN independent of HbA1c and GV metrics. Conclusion . TIR is associated with the presence of CAN independent of HbA1c and GV metrics in Chinese type 2 diabetes.